The Role of Islamic Religious Education Teachers as a Model of Character Education in SMK Negeri 1 Sambirejo - Ilham Wahyu; Nurul Latifatul Inayati (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in shaping students' character at SMK Negeri 1 Sambirejo. By using a qualitative approach and phenomenological method, this study explores the role of PAI teachers as educators, mentors, evaluators, and motivators in shaping student character. Data were collected through interviews, observations, and documentation, then analyzed by data reduction techniques, data presentation, and conclusion drawing. The results showed that PAI teachers have an important role in shaping student character through habituation of worship, exemplary, and moral and spiritual guidance. However, there are several challenges in the implementation of character education, such as low student discipline and motivation, the negative influence of the social environment, and the lack of family support. Supporting factors such as the character-based curriculum and school policies that support religious education help overcome these obstacles. This study confirms that a sustainable approach and synergy between teachers, schools and families are needed to create strong student characters that are in line with Islamic values.